Treatment and Outcomes of Thrombolysis Related Hemorrhagic Transformation: A Multi-Center Study in China - Liu, Junfeng; Wang, Yanan; Li, Jing; Zhang, Shanshan; Wu, Qian; Wei, Chenchen; Cui, Ting; Wu, Bo; Willey, Joshua Z.; Liu, Ming (Frontiers in Aging Neuroscience, 2022)
Objective To investigate the current management of thrombolysis related hemorrhagic transformation (HT) in real-world practice, and whether these treatments would reduce the risk of 3-month death and hematoma expansion after HT. Methods A multicenter retrospective study was performed in three comprehensive stroke centers in China (West China Hospital, The First People’s Hospital of Ziyang, and Mianyang Central Hospital) between January 1st 2012 and December 31th 2020. Participants were patients diagnosed with HT after intravenous thrombolytics on brain computed tomography (CT) within 36 h after stroke onset. The treatment after thrombolysis related HT included aggressive therapy (procoagulant, neurosurgical treatment) and dehydration therapy (mannitol or glycerin and fructose). The primary clinical outcome was 3-month death. The primary radiographic outcome was hematoma expansion, defined as a 33% increase in the hematoma volume using the (A × B × C)/2 method on follow-up imaging. Results Of 538 patients with ischemic stroke receiving thrombolysis included during the study period, 94 patients (17.4%) were diagnosed with HT, 50% (47/94) of whom were symptomatic HT. The 3-month death was 31.5% (29/92), with two patients having been lost to follow up. A total of 68 patients (72.3%) had follow-up brain CT scans after HT detection for evaluating hematoma expansion, of whom 14.7% (10/68) had hematoma expansion. Among the 10 patients with hematoma expansion, 7 patients were from symptomatic HT group, and 3 patients were from the asymptomatic hematoma group. In regard to escalation in therapy, six patients received neurosurgical treatment and three patients had a fresh frozen plasma infusion. In addition, dehydration therapy was the most common management after HT diagnosis [87.2% (82 of 94)]. In the multivariable models, refusing any treatment after HT diagnosis was the sole factor associated with increased 3-month death (odds ratio, 13.6; 95% CI, 3.98–56.9) and hematoma expansion risk (odds ratio, 8.54; 95% CI, 1.33–70.1). In regard to the effects of aggressive therapy, a non-significant association of receiving hemostatic/neurosurgery therapy with a lower 3-month death and hematoma expansion risk was observed (all P > 0.05). Conclusion Refusing any treatment after HT detection had a significant trend of increasing 3-month death and hematoma expansion risk after HT. Our finding of hematoma expansion among patients with asymptomatic HT in non-western populations suggests an opportunity for intervention. Very few patients after thrombolysis related HT diagnosis received procoagulant or neurosurgical therapies. Large multicenter studies enrolling diverse populations are needed to examine the efficacy of these therapies on different HT subtypes.